Expected service lives and depreciation profiles for capital assets. Evidence based on a survey of Norwegian firms - Terje Skjerpen; Nina Barth; Ådne Cappelen; Steinar Todsen; Thom Åbyholm (Statistics Norway, Research Department, 2016)
In the Norwegian national accounts, as in many other countries, it is quite common to use information on depreciation rates and profiles based on studies from the US, Canada and the Netherlands due to a lack of national studies. We present new results based on a survey of Norwegian firms concerning their perception of the expected economic service life of different types of capital assets and their assessments of the most realistic depreciation profiles. For some capital categories, information on acquisition prices and second-hand market prices were also collected, together with information on the age of capital assets when they were sold in second-hand markets. We present the companies' answers about expected service lives and depreciation profiles, and carry out an econometric analysis for two types of capital where second-hand markets exist, Machinery and equipment for mining and manufacturing, and Tools, instruments, furnishings etc. For the first group, the expected service life is estimated to be between 9 and 10 years, while, for the second group, the estimate is about 8 years. According to the descriptive analysis, the reported mean expected service lives are around 10 and 7 years, respectively. Our results are quite similar to those obtained in the literature.
Keywords: C23; C81; D24; E22; 330; Depreciation; Capital Stock; Service Lives; Survey